Instant Silverlight 5 Animation. - Polyak, Nick (Packt Publishing, 2013)
This book is written in simple, easy to understand format with lots of screenshots and step-by-step explanations. If you are a developer looking forward to create great user experience for your Silverlight applications with cool animations or create Silverlight banner ads, then this is the guide for you. It is assumed that the readers have some previous exposure to Silverlight or WPF.